Propaganda Illuminati Dalam Film Despicable Me (Analisis Semiotika Charles Sanders Peirce) - Zaeirena Humairoh (FAI, 2017)
Propaganda Illuminati Dalam Film Despicable Me (Analisis Semiotika Charles Sanders Peirce)